2019
DOI: 10.1016/j.laa.2019.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Sign matrix polytopes from Young tableaux

Abstract: Motivated by the study of polytopes formed as the convex hull of permutation matrices and alternating sign matrices, we define several new families of polytopes as convex hulls of sign matrices, which are certain {0, 1, −1}-matrices in bijection with semistandard Young tableaux. We investigate various properties of these polytopes, including their inequality descriptions, vertices, facets, and face lattices, as well as connections to alternating sign matrix polytopes and transportation polytopes.2010 Mathemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Partial alternating sign matrices are a subset of sign matrices, which differ from Definition 2.5 in that each row partial sum is not restricted to {0, 1} as in (2.5), but may equal any non-negative integer. See [19] for information about polytopes whose vertices are sign matrices and Lemma 4.9 for the relationship between these polytopes.…”
Section: Matricesmentioning
confidence: 99%
See 2 more Smart Citations
“…Partial alternating sign matrices are a subset of sign matrices, which differ from Definition 2.5 in that each row partial sum is not restricted to {0, 1} as in (2.5), but may equal any non-negative integer. See [19] for information about polytopes whose vertices are sign matrices and Lemma 4.9 for the relationship between these polytopes.…”
Section: Matricesmentioning
confidence: 99%
“…Proof. In [19,Theorem 4.3], a hyperplane is constructed that separates a given m × n sign matrix from all other m × n sign matrices. Since m × n partial alternating sign matrices are a subset of m × n sign matrices, this hyperplane must separate a given m × n partial alternating sign matrix from all others.…”
Section: Partial Alternating Sign Matrix Polytopesmentioning
confidence: 99%
See 1 more Smart Citation
“…Matrices with constraints on the sign of entries, or the sum of entries, are of interest in many settings. A sign-restricted matrix, or SRM, is an m × n (0, ±1)-matrix A such that each partial column sum, starting from row 1, equals 0 or 1, and each partial row sum, starting from column 1, is nonnegative, see [11,17]. The constraint on each column implies that its nonzeros alternate, starting with a +1.…”
mentioning
confidence: 99%
“…The constraint on each column implies that its nonzeros alternate, starting with a +1. This notion was introduced in [1] and it was shown that this class is in bijection with so-called semistandard Young tableaux (see also [17]). An important subclass of SRMs is the alternating sign matrices (ASMs); these are square SRMs where both the rows and columns are alternating starting and ending with a +1, see [2,3,6,8,9,10,18].…”
mentioning
confidence: 99%